The Influence of Environmental Factors on the Activity and Propolis Production of Tetragonula laeviceps - Salatnaya, H.; Widodo, W. D.; Winarno; Fuah, A. M. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2020)
The Environment is one of the factors influencing the development and productivity of the bee colony. Favourable environment will significantly support bee productivity. The factors which influence the bees activity include temperature, humidity, light intensity, wind speed, rainfall, and food availability. The aims of this study are to know the influence of environmental factors on activity and propolis production of stingless bees. This study used six colonies of Tetragonula laeviceps into two different locations, monoculture and polyculture nutmeg farm. The method used is a direct observation of the activities and propolis production of stingless bee and analyzed by t-test. The study results of T. laeviceps in monoculture and polyculture farms showed that the activity of the bees was influenced by environmental factors influencing propolis production. The activities would start when the temperatures ranged from 22-23 oC, humidity 70-88%, and light intensity 183-4344 lux. The peak activity of the bees occurred at the temperatures of 26-28 oC, humidity 55-71%, and light intensity 46.875-91.347 lux. The propolis produced by T. laeviceps was 27.79 g in the monoculture farm and 48.80 g in the polyculture farm. The significant difference was predominantly due to the environmental factors.